The Effect of Happiness, Education, Food Security, and Access to Information and Communication Technology on the Welfare of Indonesian Society - Zul Fikri Abdul Rozak; Mustofa Mustofa (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2025)
This study aims to determine: the influence of happiness on the welfare of the Indonesian people, the influence of education on the welfare of the Indonesian people, the influence of food security on the welfare of the Indonesian people, the influence of access to information and communication technology on the welfare of the people in Indonesia, Simultaneous tests show that each independent variable has an effect on the dependent variable. This study uses secondary data from the Indonesia Family Life Survey Wave 4 (IFLS-4) and wave 5 (IFLS-5) surveys in 2007 and 2014 which will be used as panel data in this study. The number of panel samples in IFLS-4 and IFLS-5 is 8,170 household members. The data to be analyzed includes happiness, education, food security, and access to information and communication technology. This study uses the Ordered Probit analysis method with the help of the Stata-17 application. The results of the study show that each variable has a different influence. Happiness has a positive and significant influence on the welfare of the Indonesian people, education has a negative and significant influence on the welfare of the Indonesian people, food security has a positive and significant influence on the welfare of the Indonesian people, access to information and communication technology has a negative and significant influence on the welfare of the Indonesian people, and Simultaneous tests show that each independent variable has an influence on the dependent variable.